Odpowiedzi

2009-10-24T12:56:07+02:00
(x+1)² - (y+2)² = (x-y)(x+y)
2x + y = 0

{(x²+2x+1)-(y²+4y+4)=(x²-y²)
{2x+y=0

{x²+2x+1-y²-4y-4-x²+y²=0
{y=-2x

{2x-4y-3=0
{y=-2x wstawiamy drugie r-nie do pierwszego

{2x-4*(-2x)-3=0
{y=-2x

{2x+8x-3=0
{y=-2x

{10x=3/:10
{y=-2x

{x=3/10=0,3
{y=-2*(0,3)=-0,6
Przy rozwiązywaniu wykorzystano wzory skroconego mnożenia:
(a+b)²=a²+2ab+b²-kwadrat sumy
(a-b)(a+b)=(a²-b²)-różnica kwadratów
1 5 1
2009-10-24T12:56:09+02:00
(x+1)² - (y+2)² = (x-y)(x+y)
2x + y = 0

x²+2*1*x+1² - (y²+2*2*y+2²)=x²-y²
2x+y=0

x²+2x+1-(y²+4y+4)=x²-y²
2x+y=0

x²+2x+1-y²-4y-4=x²-y²
2x+y=0

x²-y²+2x-4y-x²+y²=3
2x+y=0

2x-4y=3 /*(-1)
2x+y=0

-2x+4y=-3
2x+y=0
5y=-3 /:5
y=-3/5

2x+y=0
2x+(-3/5)=0
2x=3/5 /:2
x=3/10
Pozdrawiam:)
2 5 2
2009-10-24T12:58:08+02:00
(x+1)² - (y+2)² = (x-y)(x+y)
2x + y = 0

x² +2x +1 -y²-4y-4 = x²-y²
2x +1 -4y -4 =0

2x - 4y = 3
y= ½x -¾

2x + y = 0
y = -2x = ½x -¾

-2x = ½x -¾

-5/2 x = -¾ |*(-1)
5/2 x = ¾ |:(5/2)

x = ¾ / (5/2) = 0,3
y = -2x = -2*0.3 = -0.6